The Limitations of "One-Size-Fits-All" Instruction in Mixed-Ability ESL Classrooms: A Qualitative Case Study - Ei Zar Thin (Journal of English Education Forum (JEEF), 2026)
A qualitative case study was conducted to assess the impact of having all students receive identical lessons in ESL classes with mixed ability levels. The researcher conducted participant observation and semi-structured interviews with three ESL students who exhibited different levels of English proficiency. The purpose of the study was to evaluate how the three subjects reacted to receiving identical lessons at an identical rate, while serving as samples of the lessons provided to all ESL subjects. The researcher discovered that the best-performing student found the work boring, with no level of challenge. The intermediate student successfully completed the assigned task, but did not develop any further due to the limitations of remaining within her comfort zone. The lowest-performing student felt overwhelmed, confused, and afraid that, although the assigned task was inappropriate for him, he was unable to complete it successfully without additional assistance. Findings from this study demonstrate that the implementation of an identical lesson plan for all students does not adequately address the instructional needs of students exhibiting variable levels of English proficiency. Therefore, the study recommends adopting differentiated instruction, utilizing scaffolding, and varying the pace at which instruction occurs to better address the instructional needs of mixed-ability learners.